Simulation-based clinical learning for final year medical students about Focused Assessment Sonography for Trauma - Gun, Cem; Aldinc, Hasan (Journal of Surgery and Medicine, 2022)
Background/Aim: Point-of-care ultrasound is a focused exam. It is a method that can be easily repeated by clinicians, especially as it aims for answering specific questions. The current study aimed to evaluate how successfully the students could learn Focused Assessment with Sonography for Trauma (FAST) and the permanence of the education after the simulation-based training. Methods: This study was conducted with final year medical students in Acibadem Mehmet Ali Aydinlar University Hospital Emergency Department and Acibadem University Center of Advanced Simulation and Education. The FAST course was taught by emergency physician specialists. After 2 h of theoretical training, a 3-h hands-on small group practical session was held face-to-face in which the students performed FAST scans with a CAE Vimedix high-fidelity simulator. After ultrasound training, the participants were separated into three groups of 20 each. One group was considered a control group in which they did not perform FAST on any real patient during the emergency medicine rotation (Group A). Group B performed FAST on 20 real patients, and Group C performed the technique on 40 real patients in the emergency department. A re-evaluation exam was done six months later. Results: This study included 60 participants. At the end of the first evaluation, the mean scores of Groups A (Control Group), B, and C were 6.05 (1.72), 6.05 (1.27), and 5.55 (13.2), respectively. The second evaluation results were 2.51 (0.51) with P < 0.001) and 8.84 (0.73) with a P < 0.001, and 9.71 (0.27) with P < 0.001, respectively. Conclusion: The long-term memory retention of the training presented in the simulation alone may be controversial. In our study, the take-home point is that for 2 h of theoretical lectures and 3 h of simulation training to be permanently retained, practicing the technique with at least 20 patients is needed.